Pancreatic gastrointestinal stromal tumour with liver metastasis five years after Whipple’s procedure: a rare case with management challenges - Saleema Begum; Khan, Muhammad Rizwan (Journal of the Pakistan Medical Association, 2022)
Pancreatic gastrointestinal tumour is an unusual primary tumour of the pancreas. A 31-year-old male came to the clinic with jaundice and weight loss. Cross-sectional imaging showed a mass in the pancreatic uncinate process. Image-guided biopsy revealed gastrointestinal stromal tumour, so pancreaticoduodenectomy was performed, followed by adjuvant Imatinib. The patient had oligo-metastasis in the liver five years post-surgery and underwent liver resection. This is an unusual case where a pancreatic GIST presented with metastasis while on adjuvant treatment. Hepatectomy and multimodal therapy increases the survival if the disease is confined to the liver. Keywords: Pancreas, Gastrointestinal stromal tumour, Whipple’s procedure.